Feasibility of using fish visceral trash in a polyculture system for enhancing the growth performances of giant gourami (Osphronemus gouramy) and redclaw crayfish (Cherax quadricarinatus) - Agus Putra AS; Afrah Junita; Muhammad Jamil (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
Giant gourami and redclaw crayfish are among popular freshwater organisms with significant potential for aquaculture due to their ease of cultivation, resistance to diseases, and high economic value. Therefore, this study aimed to evaluate the feasibility of using fish visceral trash (FVT) in artificial diets to enhance the growth performances of giant gourami (Osphronemus gouramy) and redclaw crayfish (Cherax quadricarinatus) in a polyculture system. Giant gourami juveniles (3.62±0.86 cm and 3.74±1.15 g) and redclaw crayfish (3.05±0.35 cm and 6.41±0.29 g) were divided into four groups and cultured in 100 L aquarium. Each group was fed twice daily with diets containing 0%, 10%, 20%, and 30% FVT/kg diet. Furthermore, growth performances were assessed in all samples at 14 days intervals over a period of eight weeks. The results showed that diets prepared with 30% FVT significantly affected the growth rate of giant gourami juveniles, while those comprising 20% enhanced the growth of redclaw crayfish. Total length, body weight, specific growth rate, and weight gain significantly increased in samples fed with the experimental compounded diets. Based on the observations, it is suggested that using FVT compounded diets tends to improve growth performances in a polyculture system.Keywords:Giant gouramiGrowth performanceRedclaw crayfishPolycultureTrash fish